2020
DOI: 10.1080/13854046.2020.1749936
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological assessment and diagnostic disclosure at a memory clinic: A qualitative study of the experiences of patients and their family members

Abstract: Objective: The aim of this study was to gain insight into the experiences of patients and their family members regarding a neuropsychological assessment (NPA) and the diagnostic disclosure given by the medical specialist (psychiatrist, geriatrician, or their residents) at the memory clinic (MC). Method: Patients with and without a cognitive impairment and their family members were recruited from three Dutch MCs. Four focus groups with 14 patients and 13 family members were analyzed using both inductive and ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The absence of a research assistant who can verify that the examinee is focused and engaged with the task, and technical variability among tablet PC software and hardware (screen size and aspect radio, image quality, touch device sensitivity, computing power) can affect test results. Furthermore, disclosure of results in a meaningful way that is non-threatening to the examinee and promotes necessary follow-up and actions that are beneficial to their brain health is a huge and very delicate issue that must be dealt with appropriately [55][56][57]. Even if all these issues are resolved, it is still unclear if receiving a first indication through this screening method will actually lead to follow-up, further testing, and seeking of appropriate care and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a research assistant who can verify that the examinee is focused and engaged with the task, and technical variability among tablet PC software and hardware (screen size and aspect radio, image quality, touch device sensitivity, computing power) can affect test results. Furthermore, disclosure of results in a meaningful way that is non-threatening to the examinee and promotes necessary follow-up and actions that are beneficial to their brain health is a huge and very delicate issue that must be dealt with appropriately [55][56][57]. Even if all these issues are resolved, it is still unclear if receiving a first indication through this screening method will actually lead to follow-up, further testing, and seeking of appropriate care and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to participate if they were referred to the memory clinic for the evaluation of cognitive complaints and if they had had a neuropsychological assessment in the past year. More information about this procedure is described elsewhere [ 24 ]. The participants were asked for their opinions regarding these concept versions and to rank the versions according to their preference.…”
Section: Methodsmentioning
confidence: 99%
“…This is sometimes related to financial barriers but may also be due to the multidisciplinary nature of the MC [46], in which the medical specialist often communicates the diagnosis. Based on the small body of literature on experiences with a neuropsychological assessment in MC settings, a need for a follow-up consultation with the neuropsychologist has been reported [8,24,47,48]. Furthermore, providing neuropsychological feedback has been related to positive outcomes in other disorders [7].…”
Section: Experiences With Neuropsychological Feedbackmentioning
confidence: 99%
“…Most research papers used in-person feedback (Arffa & Knapp, 2008;Cheung et al, 2014;Connery et al, 2016;Fallows & Hilsabeck, 2013;Farmer & Brazeal, 1998;Foran et al, 2016;Holst et al, 2009;Kirkwood et al, 2016Kirkwood et al, , 2017Lanca et al, 2019;Lopez et al, 2008;Malla et al, 1997;Meth et al, 2016;Rosado et al, 2018;Tharinger & Pilgrim, 2012;Westervelt et al, 2007;Gruters et al, 2020;Martin & Schroeder, 2020), and most of the other publications recommended in-person feedback (Allen et al, 1986;Carone et al, 2010;Carone et al, 2013;Carone, 2017;Crosson, 2000;Gass & Brown, 1992;Gorske, 2007;Gorske & Smith, 2009;Green, 2000;Griffin & Christie, 2008;Postal & Armstrong, 2013;Ruppert & Attix, 2014). A minority gave feedback via phone (Stimmel et al, 2019), via telemedicine (Clement et al, 2001;Turner et al, 2012) or via a written report (Evans et al, 2019).…”
Section: Characteristics Of Neuropsychological Feedbackmentioning
confidence: 99%
“…Patients were more satisfied with the NPA when they received feedback, and if they experienced this as useful (Bennett-Levy et al, 1994). In one qualitative study, it was found that both positive (relief or confirmation due to NPA outcome and diagnosis) and negative experiences (feeling distressed due to awareness of cognitive complaints) coexisted during an NPA and diagnostic disclosure at a memory clinic (Gruters et al, 2020). The highest utility ratings of NPA were related to understanding cognitive strengths, weaknesses, and the relation between results and everyday behavior (Arffa & Knapp, 2008).…”
Section: Satisfaction With Neuropsychological Servicesmentioning
confidence: 99%